2009
DOI: 10.1538/expanim.58.489
|View full text |Cite
|
Sign up to set email alerts
|

The Different Effects of I.c.v. Injection of Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) on Prolactin Secretion in Adult Male and Lactating Rats

Abstract: The effects of intracerebroventricular (i.c.v.) administration of pituitary adenylate cyclase activating polypeptide38 (PACAP38) on prolactin (PRL) secretion and the activity of tyrosine hydroxylase (TH) were examined in adult male and lactating rats with or without suckling stimulus. In adult male rats and lactating rats with suckling stimulus, administration of PACAP38 (0.25 or 1 nmol) decreased PRL secretion and increased the activity of TH in the stalk-median eminence. On the other hand, the injection of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To estimate the activity of serotonergic neurons in the brain after administration of cyclophosphamide, the concentration of 5HIAA in CSF was determined by high-performance liquid chromatography (HPLC) with electrochemical detection (ECD) [3,25,29]. The mobile phase (pH 3.0) consisted of 40 mM citric acid, 40 mM dibasic sodium phosphate, 0.08 mM EDTA, 7.5 mM sodium heptanesulphonate, 4% methanol, and 2% acetonitrile [23].…”
Section: Animals and Kaolin Preparationmentioning
confidence: 99%
“…To estimate the activity of serotonergic neurons in the brain after administration of cyclophosphamide, the concentration of 5HIAA in CSF was determined by high-performance liquid chromatography (HPLC) with electrochemical detection (ECD) [3,25,29]. The mobile phase (pH 3.0) consisted of 40 mM citric acid, 40 mM dibasic sodium phosphate, 0.08 mM EDTA, 7.5 mM sodium heptanesulphonate, 4% methanol, and 2% acetonitrile [23].…”
Section: Animals and Kaolin Preparationmentioning
confidence: 99%
“…In mammals, VIP is well-documented as a stimulator for prolactin (PRL) release (Christian et al 2007) but the functional role of PACAP in PRL regulation is controversial and the data published are highly variable and contradictory to one another. For examples, the central effect via ICV injection of PACAP, which is inhibitory to PRL release in vivo (Tohei et al 2009), is different from the results of systemic administration (e.g., IV infusion) with either no effect (Sawangjaroen & Curlewis 1994) or stimulation on plasma PRL level (Jarry et al 1992). At pituitary level (e.g., in rat pituitary cells), the direct effect of PACAP on PRL regulation is also not consistent, as stimulatory (Benter et al 1995), inhibitory (Jarry et al 1992), and no effect has been reported (Hart et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, in sheep PACAP administered icv stimulated dopamine release from the tuberoinfundibular dopaminergic neurons and this effect was associated with a suppression of PRL level in the peripheral blood (138). Tohei et al (139) observed a similar effect after icv administration of PACAP to lactating rats exposed to suckling stimuli. PACAP38 decreased PRL secretion and increased the activity of thyrosin hydroxydase (TH) in ME of the pituitary stalk.…”
Section: The Effect Of Pacap On Prl Secretionmentioning
confidence: 96%